DEPDC5 variants increase fibrosis progression in Europeans with chronic hepatitis C virus infection. Issue 2 (18th December 2015) - Burza, Maria Antonella; Motta, Benedetta Maria; Mancina, Rosellina Margherita; Pingitore, Piero; Pirazzi, Carlo; Lepore, Saverio Massimo; Spagnuolo, Rocco; Doldo, Patrizia; Russo, Cristina; Lazzaro, Veronica; Fischer, Janett; Berg, Thomas; et al.
Abstract : Chronic hepatitis C virus (HCV) infection may progress to cirrhosis and hepatocellular carcinoma (HCC). Recently, two genetic variants, DEPDC5 rs1012068 and MICA rs2596542, were associated with the onset of HCC in Asian subjects with chronic HCV infection. The aim of the present study was to analyze whether DEPDC5 and MICA genetic variants were associated with liver disease progression in European subjects with chronic HCV infection. In a Northern Italian discovery cohort (n = 477), neither DEPDC5 rs1012068 nor MICA rs2596542 were associated with HCC (n = 150). However, DEPDC5 rs1012068 was independently associated with cirrhosis (n = 300; P = 0.049). The association of rs1012068 with moderate to severe fibrosis was confirmed in an independent cross‐sectional German cohort (n = 415; P = 0.006). Furthermore, DEPDC5 rs1012068 predicted faster fibrosis progression in a prospective cohort (n = 247; P = 0.027). Next, we examined the distribution of nonsynonymous DEPDC5 variants in the overall cross‐sectional cohort (n = 912). The presence of at least one variant increased the risk of moderate/severe fibrosis by 54% ( P = 0.040). To understand the molecular mechanism underlying the genetic association of DEPDC5 variants with fibrosis progression, we performed in vitro studies on immortalized hepatic stellate cells (LX‐2). In these cells, down‐regulation of DEPDC5 resulted in increased expression of β‐catenin and production of its target matrix metallopeptidase 2 (MMP2), a secreted enzyme involved in fibrosis progression. Conclusion: DEPDC5 variants increase fibrosis progression in European subjects with chronic HCV infection. Our findings suggest that DEPDC5 down‐regulation may contribute to HCV‐related fibrosis by increasing MMP2 synthesis through the β‐catenin pathway. (Hepatology 2016;63:418–427)